1995
DOI: 10.1007/bf01298899
|View full text |Cite
|
Sign up to set email alerts
|

Cross sections for (n, p) reaction on zinc isotopes in terms of the novel multistep compound reaction model

Abstract: Abstract.Cross sections for the (n,p) reaction on 64'66'67'68Zn isotopes have been measured by the activation method and successfully described in terms of the statistical multistep direct and the novel statistical multistep compound reaction model. PACS: 25.40.Fq

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Here, the quoted uncertainty is the result of the combined uncertainties of statistical and systematic errors, such as the -ray yield statistics (4.9%), the -ray detection efficiency of the HPGe detector (3.0%), the -ray emission probability (5.6%), and the 93 Nb(n,2n) 92m Nb cross section for the normalization of the neutron intensity (2.5%), respectively. The present result agrees with those obtained by Konno et al 24) and Ghorai et al 25) (the result at 15.2 MeV) within experimental uncertainty, but slightly differs from those obtained by Viennot et al 26) and Kielan and Marcinkowski,27) as shown in Table III. This difference, however, could be solved using the latest result of -ray emission probability, as discussed below.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Here, the quoted uncertainty is the result of the combined uncertainties of statistical and systematic errors, such as the -ray yield statistics (4.9%), the -ray detection efficiency of the HPGe detector (3.0%), the -ray emission probability (5.6%), and the 93 Nb(n,2n) 92m Nb cross section for the normalization of the neutron intensity (2.5%), respectively. The present result agrees with those obtained by Konno et al 24) and Ghorai et al 25) (the result at 15.2 MeV) within experimental uncertainty, but slightly differs from those obtained by Viennot et al 26) and Kielan and Marcinkowski,27) as shown in Table III. This difference, however, could be solved using the latest result of -ray emission probability, as discussed below.…”
Section: Resultssupporting
confidence: 82%
“…64 Cu reaction, { 64 Zn(n,p) 64 Cu}, is in the range from 134 to 217 mb at 14:5 < E n < 14:8 MeV, [24][25][26][27] the cross section of the 67 Zn(n,p) 67 Cu reaction, { 67 Zn- (n,p) 67 Cu}, is in the range from 38 to 107 mb at E n $ 14 MeV, [24][25][26][27] and the cross section of the 68 Zn(n,x) 67 Cu reaction, { 68 Zn(n,x) 67 Cu}, is reported to be 2.1 mb 28) and 7.67 mb 24) at E n % 14:7 MeV. The origins of the large discrepancies in the reported cross sections between the different datasets are not yet clear, since they have not been discussed in published papers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the accurate cross sections data of 89 Y are needed to examine how these materials are affected by neutrons in nuclear reactor [5]. Yttrium is also one of the important fusion reactor material, whose neutron induced reaction cross-section is necessary to determine within the energies of 12-20 MeV [4,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…The cross sections data for 67 Zn(n,p) 67 Cu [6][7][8][9], 64 Zn(n,2n) 63 Zn [1,3,7,[10][11][12][13], 89 Y(n,γ) 90m Y [4,[14][15][16][17], 89 Y(n,2n) 88 Y [5,7,10,[18][19][20][21][22][23] reactions are available around the neutron energy of 14 MeV. However, there is comparably huge disagreement [1,8,9,17] and ambiguity in the experimental data, which is most probably due to various nuclear parameters like half-life, γ-ray abundances, monitor cross section and types of detectors used.…”
Section: Introductionmentioning
confidence: 99%
“…7. We fit the activation cross sections of 67 Znðn; pÞ reaction obtained by Kielan et al 83) around 14 MeV, while their cross sections above 15.4 MeV become larger than the evaluated results. Figure 7 shows that the present evaluation supports the smaller cross sections at 14 MeV, considering the experimental data at lower incident energies.…”
Section: )mentioning
confidence: 99%